THE INFLUENCE OF PRODUCTS AND PROMOTIONS ON PURCHASE DECISIONS STUDY CASE IN PT. XYZ - Annisa Audina Purba; Rulianda Purnomo Wibowo; Yeni Absah (CV. RADJA PUBLIKA, 2025)
In the world of marketing, consumer purchasing decisions are greatly influenced by various factors, one of which is the product and promotion offered by the company. Therefore, it is important for companies to understand how these two factors can influence consumer behavior in making purchasing decisions. This study aims to investigate the Influence of Products and Promotions on Yakult Purchasing Decisions Case Study of PT. Yakult Medan Branch This type of research is quantitative. The number of samples in this study was 100 respondents. The data analysis techniques used in this study were research instrument tests (validity and reliability), descriptive statistical tests, classical assumption tests (normality, multicollinearity and heteroscedasticity), and hypothesis tests (multiple linear analysis tests, t-tests, F-tests and coefficients of determination) with the help of SPSS version 26. The results of this study indicate that Products (X1) have a positive and significant effect on Purchasing Decisions (Y), Promotions (X2) have a positive and significant effect on Purchasing Decisions (Y) and Products (X1) and Promotions (X2) have a positive and significant effect simultaneously on Purchasing Decisions (Y) at PT. Yakult Indonesia Persada Medan Branch.